First record of Hemidactylus mabouia (Moreau de Jonnès, 1818) (Squamata, Gekkonidae) from Colonia Carlos Pellegrini (Corrientes) and Salvador Mazza (Salta) in Argentina - Vanesa Chocobar; Carolina Lobo Terán; Fernando Lobo; Matías Quipildor; Soledad Ruiz; Soledad Valdecantos (Check List, 2023)
Hemidactylus mabouia (Moreau de Jonnès, 1818) is an African species introduced and widely distributed in South America. We report H. mabouia for the first time in the municipal campsite of Colonia Carlos Pellegrini (province of Corrientes, Argentina) and in Salvador Mazza (province of Salta, Argentina). These new records increase the known distribution in Argentina of this invasive species, and they are the first from Salta, and only the second from Corrientes.